Pendampingan Penulisan Makalah Ilmiah bagi Mahasiswa Baru Program Studi Manajemen Pendidikan Islam UIN Walisongo Semarang - Naharani, Ita (Jurnal Penelitian dan Pengabdian Masyarakat, 2024)
This community service activity aims to improve the understanding and abilities of new students of the Islamic Education Management study program so that they can gain experience, understanding and abilities regarding writing scientific papers which can later be useful for students. The methods used include lecture, discussion and simulation methods. This Community Service Activity was carried out on August 30, 2024 in the Theater room (IsDB FSH) UIN Walisongo Semarang. Based on the results of the activities that have been carried out, it shows the enthusiasm of new students of the Islamic Education Management study program in participating in activities so that students better understand the material on writing scientific papers